Tinggalan Tradisi Megalitik Situs Watugong, Kelurahan Tlogomas, Kecamatan Lowokwaru, Kota Malang: Kajian Bentuk, Fungsi, dan Makna - Nabil Naufal Alghifari; Rochtri Agung Bawono; I Ketut Setiawan (KALPATARU, 2022)
There are remnants of late prehistoric life in the Greater Malang, one of which is located in the Metro  watershed, which stretches from Malang City's west to south. The area was once inhabited during the Megalithic period, as evidenced by the remains of the megalithic tradition along the Metro watershed, which was considered a holy river for its rich natural resources. Watugong Village is a human settlement area that supported the megalithic tradition because it has a cultural heritage site from the end of the  Neolithic era to the arrival of the Hindu-Buddha period. This research aims to determine the form, function, and meaning of the megalithic tradition remains found at Watugong Site. Researchers used descriptive-morphological analysis, accompanied by an analysis of contextual relationships between the megalithic remains on the site and the surrounding environment and findings, then did comparative analysis to compare research object data with other similar research objects, and ethnoarchaeological analysis to find out the meaning of the continuous rituals to preserve the beliefs of their ancestors that are still carried out by the local community. The results obtained were that the archaeological remains at Watugong Site are of a megalithic pattern with a cross-time context at the same time as the Hindu-Buddhist influence began to enter the Watugong Village area, and the tradition of honoring ancestors derived from the megalithic tradition is still carried out today by the local community.